Bleaching powders, bleaching creams and other hair lightening preparations as sources for (airborne) allergic contact dermatitis and other health effects in hairdressers: Results of an empirical study - Symanzik, Cara; Koopmann, Kirsten; Skudlik, Christoph; John, Swen M.; Uter, Wolfgang (Contact Dermatitis, 2022)
Background Various products are available for lightening hair. There are no data on which applications are actually used in hairdressing, impeding proper estimation of actual exposure and necessary preventive measures. Objectives To assess information about availability, usage and formulation of lightening preparations in the German hairdressing trade. Methods A market survey was conducted and hairdressers were surveyed by online questionnaires. Results Of 783 hairdressers clicking the link, 565 hairdressers (91.2% female, mean age of 40.2 +/- 11.7 years) from all German states responded (response rate: 72.2%). The questionnaire survey has shown that available hair-lightening preparations in the German hairdressing trade are (multiple selection possible): dust-free (88.5%) and non-dust-free bleaching powders (22.1%), bleaching creams (41.9%), high-lifting hair colour creams (88.8%) and normal hair colour creams (58.4%). Five hundred eighteen (91.7%) hairdressers favour lightening hair with powder. The market survey revealed that bleaching powders and creams contain potassium persulfate, ammonium persulfate and sodium persulfate or combinations of these persulfate salts. Conclusions Hairdressers are exposed to various hair-lightening applications containing different chemicals. Preventive measures need to address adverse skin and respiratory effects. Implementation of targeted health education already in early career stages (i.e., apprenticeship) seems advisable and can be maintained by refresher trainings.
CRIS-Team WoS Importer:2022-12-02